Association of Gallbladder Polyp with the Risk of Colorectal Adenoma - Jung Won Jeun; Jae Myung Cha; Joung Il Lee; Kwang Ro Joo; Hyun Phil Shin; Jun Uk Lim (Intestinal Research, 2014)
Background/AimsGallbladder polyps and colorectal adenomas share many common risk factors; however, their association has never been studied. The aim of this study was to investigate this association in asymptomatic healthy subjects.MethodsConsecutive asymptomatic subjects who underwent both screening colonoscopy and abdominal ultrasonography at Kyung Hee University Hospital in Gang Dong between July 2010 and April 2011 were prospectively enrolled. The prevalence of colorectal adenoma was compared between subjects with or without gallbladder polyps. Furthermore, a logistic regression analysis was performed to determine the independent risk factors for colorectal adenoma in these subjects.ResultsOf the 581 participants, 55 presented with gallbladder polyps and 526 did not have gallbladder polyps. Participants with gallbladder polyps showed a trend toward a higher prevalence of colorectal adenoma than those without gallbladder polyps (52.7% vs. 39.2%, P=0.051). Although the result was not statistically significant, gallbladder polyps were found to be a possible risk factor for colorectal adenoma (odds ratio=1.796, 95% confidence interval=0.986-3.269, P=0.055), even after adjusting for potential confounding factors. There was no difference observed in colorectal adenoma characteristics between the two groups.ConclusionsOur results suggest a possible association between gallbladder polyps and colorectal adenomas. Future studies with larger cohorts are warranted to further investigate this matter.